Anti–SARS-CoV-2 Monoclonal Antibodies for Early COVID-19: A Real-World Experience. Issue 2 (27th March 2022) - Belden, Katherine A.; Hess, Bryan; Brugger, Caroline; Carr, Rachel; Braun, Todd; DeRose, Joseph; Zurlo, John
Abstract : Background: Anti–SARS-CoV-2 monoclonal antibodies have been shown to reduce severe COVID-19 in high-risk ambulatory patients. Methods: This operations study at 3 affiliated centers conducted from November 23, 2020, to April 30, 2021, identified and treated patients meeting criteria for anti–SARS-CoV-2 monoclonal antibody therapy. The primary study outcome was treatment of qualifying patients. Secondary outcomes included infusion complications, hospitalization/death, and symptom resolution. Results: Three hundred sixty-seven patients were treated during the study period. The mean patient age was 63 years (SD, 13.47 years). A total of 201 patients (55%) were male, 276 patients (75%) were White, 54 patients (15%) were African American, 10 patients (2.7%) were Asian, and 9 patients (2.4%) identified as Latino or Hispanic. Patients had a first positive direct SARS-CoV-2 test within 10 days of infusion and met high-risk criteria with 232 patients (63%) having more than 1 risk factor. Thirty-two patients (9%) had received at least 1 dose of SARS-CoV-2 vaccination. Four patients experienced an infusion reaction. Of 236 patients reporting time to symptom resolution, 172 patients (73%) were symptom free within 5 days of infusion. Twenty patients (5%) treated were hospitalized for COVID-19 within 30 days of infusion including 1 patient death from COVID-19. Conclusions: Our study demonstrates that treatment with anti–SARS-CoV-2 neutralizing monoclonal antibodies is feasible in a high-resource health care setting. Infusion was well tolerated by the majority of patients, and there were no known infusion center SARS-CoV-2 exposures.